2021
DOI: 10.1200/go.20.00425
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Sub-Saharan Africa

Abstract: More than 80% of global hepatocellular carcinoma (HCC) patients are estimated to occur in sub-Saharan Africa (SSA) and Eastern Asia. The most common risk factor of HCC in SSA is chronic hepatitis B virus (HBV) infection, with the incidence highest in West Africa. HBV is highly endemic in SSA and is perpetuated by incomplete adherence to birth dose immunization, lack of longitudinal follow-up care, and impaired access to antiviral therapy. HBV may directly cause HCC through somatic genetic alterations or indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…The hepatocellular carcinoma (HCC) remains one of the most frequent cancers in Africa. 1,2 Globally, the chronic carriage of the hepatitis B virus (HBV) or hepatitis C virus (HCV) are major etiological factors of liver cancers. The HBV infection would be responsible of half of all cases of HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatocellular carcinoma (HCC) remains one of the most frequent cancers in Africa. 1,2 Globally, the chronic carriage of the hepatitis B virus (HBV) or hepatitis C virus (HCV) are major etiological factors of liver cancers. The HBV infection would be responsible of half of all cases of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection share the same vulnerable groups with the HIV infection, which include injectable drug users, men who have sex with men, hemodialysis patients, health care workers and children born to mothers carrying the surface antigen of the HBV (HbsAg positive). 2,4,5 In Burkina Faso, according to GLOBOCAN, the primary liver cancer would be the third most frequent cancer (following the cervical and breast cancer). It would be the second cause of mortality by cancer following the cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to resource limitation, surveillance might still be difficult to achieve despite sufficient physicians’ knowledge and proactive attitudes toward surveillance, and these were also documented as barriers in many other countries with limited resources. [17] One of the possible causes of inadequate healthcare resources might be due to insufficient healthcare fundings. It was shown that low- and middle-income countries distributed smaller funds to healthcare expenditures than high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HCC in Africa have among the lowest reported survival rates in the world, particularly when compared to patients from higher income countries [ 69 , 70 ] . A major contributor to this wide disparity in mortality is late presentation and diagnosis, in addition to a relative paucity of disease screening and HCC surveillance.…”
Section: Hcc Surveillance In Hiv-hbv Coinfected Patientsmentioning
confidence: 99%